2011 ACCF/AHA/SCAI Guideline for Percutaneous Coronary Intervention. A report of the American College of Cardiology Foundation/American Heart Association Task Force on Practice Guidelines and the Society for Cardiovascular Angiography and Interventions - Levine, Glenn N; Bates, Eric R; Blankenship, James C; Bailey, Steven R; Bittl, John A; Cercek, Bojan; Chambers, Charles E; Ellis, Stephen G; Guyton, Robert A; Hollenberg, Steven M; Khot, Umesh N; Lange, Richard A; et al. (Journal of the American College of Cardiology, 2011)
An organized and directed approach to a thorough review of evidence has resulted in the production of clinical practice guidelines that assist physicians in selecting the best management strategy for an individual patient. [...]clinical practice guidelines can provide a foundation for other applications, such as performance measures, appropriate use criteria, and both quality improvement and clinical decision support tools. For certain conditions for which inadequate data are available, recommendations are based on expert consensus and clinical experience and are ranked as LOE C.\n ACS = acute coronary syndromes AKI = acute kidney injury BMS = bare-metal stent(s) CABG = coronary artery bypass graft surgery CAD = coronary artery disease CKD = chronic kidney disease CTO = chronic total occlusion DAPT = dual antiplatelet therapy DES = drug-eluting stent(s) ECG = electrocardiogram EF = ejection fraction EPD = embolic protection device FDA = U.S. Food and Drug Administration FFR = fractional flow reserve GDMT = guideline-directed medical therapy GI = gastrointestinal GP = glycoprotein IABP = intra-aortic balloon pump IV = intravenous IVUS = intravascular ultrasound LAD = left anterior descending LIMA = left internal mammary artery LV = left ventricular LVEF = left ventricular ejection fraction MACE = major adverse cardiac event MI = myocardial infarction MRI = magnetic resonance imaging NCDR = National Cardiovascular Data Registry PCI = percutaneous coronary intervention PPI = proton pump inhibitor RCT = randomized controlled trial SIHD = stable ischemic heart disease STEMI = ST-elevation myocardial infarction SVG = saphenous vein graft TIMI = Thrombolysis In Myocardial Infarction TMR = transmyocardial laser revascularization UA/NSTEMI = unstable angina/non-ST-elevation myocardial infarction UFH = unfractionated heparin * This table represents the relationships of reviewers with industry and other entities that were disclosed at the time of peer review and determined to be relevant.